Dim light at night: physiological effects and ecological consequences for infectious disease. (23rd June 2018) - Kernbach, Meredith E; Hall, Richard J; Burkett-Cadena, Nathan D; Unnasch, Thomas R; Martin, Lynn B
Abstract: Light pollution has emerged as a pervasive component of land development over the past century. Several detrimental impacts of this anthropogenic influence have been identified in night shift workers, laboratory rodents, and a plethora of wildlife species. Circadian, or daily, patterns are interrupted by the presence of light at night and have the capacity to alter rhythmic physiological or behavioral characteristics. Indeed, biorhythm disruption can lead to metabolic, reproductive, and immunological dysfunction depending on the intensity, timing, duration, and wavelength of light exposure. Light pollution, in many forms and by many pathways, is thus apt to affect the nature of host–pathogen interactions. However, no research has yet investigated this possibility. The goal of this manuscript is to outline how dim light at night, a relevant and common form of light pollution, may affect disease dynamics by interrupting circadian rhythms and regulation of immune responses as well as opportunities for host–parasite interactions and subsequent transmission risk including spillover into humans. We close by proposing some promising interventions including alternative lighting methods or vector control efforts.